Evaluation tool for road safety campaigns – a short overview - Marko Divjak; Vlasta Zabukovec (Psihološka Obzorja, 2011)
The aim of this paper is to introduce the Evaluation tool for road safety campaigns which is one of the most important results of the CAST project. Recommendations and guidelines of the Evaluation tool are based on the fact that certain attributes (the scope of a campaign, the target group(s), the goals and the activities of a campaign) of a campaign have a detrimental effect upon designing evaluation, which means choosing suitable measurement variables, data collection methods/techniques and research designs. Recommendations and guidelines about various options for evaluation are given for each of the four attributes separately. The Evaluation tool guides evaluator through the process by emphasizing the approaches that appear most useful in a given context together with the main strengths and weaknesses.